Sixty years of the Revista Peruana de Ginecología y Obstetricia, 1955-2015 - Pacheco Romero, José (2016)
A review of editorial occurrences since 1955 when the journal Ginecología y Obstetricia was first published until 2015 is done, mentioning its continuity and permanence with publication of articles on obstetrics and gynecology, reproduction, infertility, public health, neoplasias, and fetal medicine. The presence of the current Editorial Committee since 1994 has allowed editorial quality, permanence, peer review, visibility, impact, and citations, incentivizing research and publication, and obtaining digitalization of all articles of the Revista Peruana de Ginecología y Obstetricia in the Open Journal System since 1955.